Penyuluhan Pengendalian Organisme Pengganggu Tanaman Manggis (Garcinia Mongostana L) Secara Terpadu Pada Kelompok Tani Mukti di Desa Cibuntu Kecamatan Wanayasa Kabupaten Purwakarta - Sulandjari, Kuswarini; Purnama, Reza Wahyu (Jurnal Budiman: Pembangunan dan Pengabdian Masyarakat Nusantara, 2023)
Cibuntu is a mangosteen-producing village. Fluctuations and low mangosteen production are caused by pests. Most farmers have not implemented IPC to the fullest. This extension aims to change and improve the understanding, willingness of farmers and the application of IPM. The target of the extension is the members of the Mukti Farmers Group. The The executors are the POPT field staff of the West Java BPTPH agency. Held since 2020. The extension materials include types of organisms that disturb mangosteen plants, the concept of integrated pest control. Anjangsono counseling methods, lectures, discussions, demonstrations of how to, demonstration of results and installation of banners. As a result of counseling, there is an increase in the number of farmers who know the concept of controlling pests, know how to control opto mangosteen in an integrated manner, about natural enemies and integrated opt control is an efficient way. Farmers who have doubts about the concept of opt and how to control integrated opt and about natural enemies are decreasing in number. There are 13.3% of farmers who still don't know how to do IPM. There is an increasing number of farmers who agree to the conservation of natural enemies, weeding tools is better than with pesticides, destroying diseased crop residues, and not eating and drinking when applying pesticides. There was a decrease in the number of farmers who used inorganic pesticides and left the plants alone and did not wash the remaining pesticide mixture. There was an increase in the number of farmers who washed the remaining pesticide mixture first. There was no change in the number of farmers who washed their body parts affected by pesticides with running water or detergent.